2021
DOI: 10.1038/s41598-021-95865-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and all-cause, cardiovascular disease, and respiratory mortality in older people in the UK and USA

Abstract: Preventing deterioration of oral health in older age can be crucial for survival. We aimed to examine associations of oral health problems with all-cause, cardiovascular disease (CVD), and respiratory mortality in older people. We used cohort data from the British Regional Health Study (BRHS) (N = 2147, 71–92 years), and the Health, Aging and Body Composition (HABC) Study (USA) (N = 3075, 71–80 years). Follow-up was 9 years (BRHS) and 15 years (HABC Study). Oral health comprised tooth loss, periodontal disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 54 publications
4
35
0
1
Order By: Relevance
“…Edentulism is associated with nutritional deficits and significantly impacts the quality of life of the elderly; data from literature associates edentulism with increased mortality. Edentulism is highly associated in elderly population with the access to dental care services, offered by the state of public financial support or implementation of dental care policies [ 39 , 40 , 41 ]. Edentulism is highly prevalent around the world; 21.9% of patients over 74 in the United States of America and 39.6% from the same age group in New Zealand are affected by this condition.…”
Section: Oral Pathology In the Elderly Patientmentioning
confidence: 99%
“…Edentulism is associated with nutritional deficits and significantly impacts the quality of life of the elderly; data from literature associates edentulism with increased mortality. Edentulism is highly associated in elderly population with the access to dental care services, offered by the state of public financial support or implementation of dental care policies [ 39 , 40 , 41 ]. Edentulism is highly prevalent around the world; 21.9% of patients over 74 in the United States of America and 39.6% from the same age group in New Zealand are affected by this condition.…”
Section: Oral Pathology In the Elderly Patientmentioning
confidence: 99%
“…In a study by Kotronia et al involving 5222 elderly subjects who were followed for an average of 9–15 years, it was shown that the presence of PD increased the risk of cardiovascular mortality by 49% (HR = 1.49; 95% CI: 1.01–2.20) [ 108 ]. Similar results were obtained by Bengtsson et al in a study involving 858 subjects over 60 years of age who were followed for an average of 17 years, it was shown that PD increased the risk of CAD (HR = 1.5; CI: 1.1–2.1) and cardiovascular death (HR = 1.4, 95% CI: 1.2–1.8) [ 109 ].…”
Section: Periodontal Disease and Risk Of Atherosclerosis Cardiovascul...mentioning
confidence: 99%
“…The Hemi-desmosomes (multi-protein complexes) and desmosomes (adhesive proteins) both are basic key factors of cell-cell junction. The innate immune response activation and invasion of virulence factors affect these basic structures, which leads to the break-down of epithelial barriers [56]. Through this, the bacterium migrates from the cell-cell junctions and makes the whole blood vessel more permeable.…”
Section: Different Line-host Defense In Between Bacterial Pathogens A...mentioning
confidence: 99%